2009
DOI: 10.1007/s00432-009-0587-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of angiotensin I converting enzyme inhibitors and angiotensin II type 1 receptor blockers on survival in patients with advanced non-small-cell lung cancer undergoing first-line platinum-based chemotherapy

Abstract: Addition of ACEI or ARB to platinum-based first-line chemotherapy may contribute to prolonged survival in patients with advanced lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 34 publications
(41 reference statements)
10
124
0
1
Order By: Relevance
“…In a retrospective cohort study of advanced non-small-cell lung cancer, RAS inhibitors were statistically associated with longer survival when used with first-line platinum-based chemotherapy. (29) Cimetidine, the prototypical histamine H2 receptor antagonist, has shown antitumor activity against colon, gastric and kidney cancers and melanomas. (17) Multiple potential mechanisms have been indicated: (i) a direct inhibitory effect on tumor growth by blocking the cell-growth-promoting activity of histamine; (ii) an indirect effect by inhibiting tumor-associated angiogenesis; and (iii) a cell-mediated immunomodulation by enhancing the host's immune responses to tumor cells.…”
Section: (A) (B) (C) (D) (E) (F)mentioning
confidence: 99%
“…In a retrospective cohort study of advanced non-small-cell lung cancer, RAS inhibitors were statistically associated with longer survival when used with first-line platinum-based chemotherapy. (29) Cimetidine, the prototypical histamine H2 receptor antagonist, has shown antitumor activity against colon, gastric and kidney cancers and melanomas. (17) Multiple potential mechanisms have been indicated: (i) a direct inhibitory effect on tumor growth by blocking the cell-growth-promoting activity of histamine; (ii) an indirect effect by inhibiting tumor-associated angiogenesis; and (iii) a cell-mediated immunomodulation by enhancing the host's immune responses to tumor cells.…”
Section: (A) (B) (C) (D) (E) (F)mentioning
confidence: 99%
“…A recent cohort study has also demonstrated a lower incidence of cancer in patients using ACE-I or an AT-II receptor blocker (ARB) than nonusers [40]. Furthermore, it has been reported that the addition of ACE-I or ARB provided the prolonged survival for the patients with advanced non-small cell lung cancer undergoing platinum-based chemotherapy [41]. Additionally, inhibition of RAAS possibly exerted the beneficial effects on the prognosis of patients with advanced hormone-refractory prostate cancer and pancreatic cancer receiving gemcitabine [42,43].…”
Section: Raas Blockersmentioning
confidence: 99%
“…Direct ACE signaling has also been reported (76,77), although its involvement in angiogenesis has not been described. Currently, ACE inhibitors are receiving attention as potential additional therapy to standard chemotherapeutic regimen with the proposed mechanism being angiogenesis inhibition (102,148). However, the effect of ACE via AT 1 Rmediated angiogenesis is insufficient to account for the reported discrepancies on the role of ACE inhibitors in cancer.…”
Section: Renin Angiotensin System and Angiogenesismentioning
confidence: 99%
“…Clinically, a number of retrospective studies have shown that ACE inhibitor use is associated with reduced cancer risks (28,81,145). ACE inhibition in combination with other therapies have been found to improve outcome in certain tumors such as pancreatic (102) and nonsmall lung cancer (148), with AT 1 R-mediated regulation of downstream genes associated with angiogenesis being a proposed mechanism (64,139). However, there are also abundant studies that suggest neutral or even negative impact of ACE inhibitor or RAS blocker use on specific cancers in clinical models (6,132,153).…”
mentioning
confidence: 99%